A Critical Theory Perspective On Sustainability Efforts - Rachman, Tutut Arif; Winarno, Agung (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The development of an increasingly advanced era, along with more and more human needs that must be met to achieve better expectations, but it also has an impact on nature which is starting to erode. Human exploitation of natural resources continues to cause concern, so environmental conservation and environmental sustainability efforts are needed. Both of these are not only the responsibility of certain parties but of each of us individually. Each individual must have critical thinking to play a role in the idealism of criticizing environmental damage. This research will use the scoping review method to map the perspectives of critical theory to respond to the problems of conservation and environmental sustainability. The critical theory perspective explores how political, economic, social and cultural challenges affect efforts to mitigate environmental damage.